Economic behavior of indigenous peoples: The Mexican case - Juan Carlos Pérez Velasco Pavón (Latin American Economic Review, 2014)
Indigenous peoples have three features in common: their historical heritage, their current culture and their extreme poverty. This paper presents a hypothesis about the development of a cultural factor: indigenous people prefer to work on a small scale. This cultural factor developed during the colonial period and remains a part of current indigenous culture. To test the hypothesis, I elaborated a trade model and an economic growth model that take into account the cultural factor. As predicted, the results help to explain indigenous peoples' poverty. This article includes empirical evidence about Mexico's indigenous population.
Keywords: Z13; D01; F1; O41; 330; Cultural trails; Tradition; Microeconomic behavior; Firm behavior; Trade; Economic growth